PENGARUH MANAJEMEN KELAS DAN ETOS KERJA GURU TERHADAP EFEKTIVITAS BELAJAR SISWA DI SMA BUDI UTOMO KOTA LUBUKLINGGAU - Aisyah Asmarajaya; Supardi Supardi (Jurnal Interprof, 2018)
This research is a quantitative research with the aim to know the influence of classroom management and work ethic of teacher to student's learning effectivity in Senior High School (SMA) Budi Utomo Lubuklinggau, forThe F count obtained is 10.458> F table = 2.051 and the significance level simultaneously significance is 0,000 <(α) = 0,05 df = n - k = 30 - 2 - 1 = 27 is 2.051 so Ho is rejected and Ha be accepted. means that simultaneously the independent variables X1 (classroom management) and X2 (work ethic of teachers) have a significant influence on the dependent variable Y (student learning effectiveness) to be proven true and hypothesis acceptable. From result of t test for class management variable (X1) to teacher performance show value t count = 3,652 bigger than t table value 2,048 with significant level = 0,001 <(α) 0.05, df (n-2) 30 - 2 = 28 is 2.048, this shows Ho is rejected and Ha accepted and partially classroom management variables have a significant effect on the effectiveness of student learning in Senior High School Budi Utomo Lubuklinggau City. From t test result for teacher work ethic variable (X2) to student's learning effectiveness (Y) shows tct value = 2,512 bigger than ttable value 2.048 with significant level = 0,000 <(α) 0.05, df (n-2) 30 - 2 = 28 is 2.048, this indicates Ho is rejected and Ha accepted and partially variable work ethic of teacher have a significant influence to the effectiveness of student learning in Senior High School Budi Utomo Lubuklinggau City